Developing Correctional Policy, Practice, and Clinical Care Considerations for Incarcerated Transgender Patients Through Collaborative Stakeholder Engagement. (July 2019) - Kendig, Newton E.; Cubitt, Andrea; Moss, Andora; Sevelius, Jae
Transgender persons are at increased risk of victimization during incarceration and have unique health care needs. We convened a symposium of 27 key stakeholders to develop consensus on correctional policy, practice, and clinical care considerations for incarcerated transgender persons. Participants included formerly justice-involved transgender persons, correctional leaders, government authorities, academicians, advocates, health care providers, and expert consultants. Consensus considerations were developed in four areas: correctional practices that promote safety and respectful interactions with transgender inmates, training of correctional staff, health care delivery, and reentry to the community. Gaps in knowledge and practice in these four areas were also identified. A collaborative stakeholder model is an effective strategy to convene disparate groups who infrequently communicate with one another to help advance correctional policies and clinical care.